PENGARUH KEPUTUSAN INVESTASI DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2013 - Maiyaliza Maiyaliza (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
Optimization of corporate value is obtained, among others, by implementing financial management functions, in which a financial decision affects the others, which eventually affects the corporate value. This research aimed to analyze the effect of investment decision and dividend policy to firm value at banking companies registered in Indonesia Stock Exchange. The population of this research are 41 banking companies registered in Indonesian Stock Exchange. The sampling method used is which purposive sampling. The sample consisted of 6 banking companies registered in Indonesian Stock Exchange with the 2009-2013 financial reporting period or of 5 years, so the total data that is 30 data sampel panel. Data analyzed using classic assumption test and hypothesis testing using multiple linear regression analysis. The analysis of data is using statistical software SPSS 16 for windows. The study resulted that partially investment decisions had a positive influence and significant as big as 34,8% to firm value. However, dividend policy had a negative influence and significant as big as 33,6% to firm value. Simultaneously, investment decisions and dividend policy had a positive influence and significant as big as 68,4% to firm value, while the remaining as big as 31,6% are other variables besides the contribution of the variables used by researchers. Key words : Investment Decisions, Dividend Policy, Firm Value.